Pengaruh Persepsi Kemudahan, Persepsi Kebermanfaatan, dan Sikap Terhadap Minat Penggunaan Layanan Fintech Crowdfunding Syariah Studi Kasus Masyarakat Jabodetabek - Muhammad Riduan Hidayat; Nurizal Ismail (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, and attitude on the interest in using Sharia fintech crowdfunding services in the Jabodetabek community. This research employs a quantitative method with purposive sampling on 100 respondents. The research instrument consists of a structured questionnaire with a Likert scale of 1-5, and data analysis is conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that all three variables significantly influence the interest in using Sharia fintech crowdfunding services. Perceived ease of use, perceived usefulness, and a positive attitude enhance public interest in adopting this service. This study confirms the complexity of factors affecting the adoption of Sharia financial technology and provides insights for the development of Sharia fintech crowdfunding in Indonesia.